2007
DOI: 10.1093/pan/mpm014
|View full text |Cite
|
Sign up to set email alerts
|

Does Voting by Mail Increase Participation? Using Matching to Analyze a Natural Experiment

Abstract: This paper examines how the growth in vote-by-mail and changes in voting technologies led to changes in the residual vote rate in California from 1990 to 2010. We find that in California's presidential elections, counties that abandoned punch cards in favor of optical scanning enjoyed a significant improvement in the residual vote rate. However, these findings do not always translate to other races. For instance, find that the InkaVote system in Los Angeles has been a mixed success, performing very well in pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(87 citation statements)
references
References 38 publications
4
82
0
1
Order By: Relevance
“…The first approach follows Kousser and Mullin (2007) and uses the full set of precincts but preprocesses the data using Mahalanobis distance matching (Ho et al 2007). The second approach, which is based upon a regression discontinuity design (RDD), compares the outcomes we observe in precincts that are just above the 250-registrant threshold with outcomes we observe in precincts that are just below the 250-registrant threshold.…”
Section: Description Of the Empirical Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…The first approach follows Kousser and Mullin (2007) and uses the full set of precincts but preprocesses the data using Mahalanobis distance matching (Ho et al 2007). The second approach, which is based upon a regression discontinuity design (RDD), compares the outcomes we observe in precincts that are just above the 250-registrant threshold with outcomes we observe in precincts that are just below the 250-registrant threshold.…”
Section: Description Of the Empirical Approachesmentioning
confidence: 99%
“…In this study, we leverage an election administration policy in California, previously identified by Kousser and Mullin (2007), which produces some variation in the use of VBM that approximates such an experiment. 5 Briefly, the California Election Code permits county elections officials to require all voters to use VBM if a precinct contains 250 or fewer registered voters (hereafter, ''VBM-only'' precincts).…”
mentioning
confidence: 99%
“…The effects of electoral rules have acquired new relevance in the wake of the Supreme Court decision in Shelby County v. Holder (2013), which invalidated a key section of the 1965 Voting Rights Act, allowing many more jurisdictions to amend electoral rules without federal oversight. As Kousser and Mullin (2007) observe, the United States is cross-cut by boundaries for elections at the local, state, and federal levels. Besides variation in registration deadlines, U.S. elections differ in myriad ways, such as the presence or absence of voter ID laws (Bentele and O'Brien 2013), the availability of mail ballots, sample ballots, and other information (Wolfinger, Highton, and Mullin 2005;Kousser and Mullin 2007), or the accessibility of polling places (Brady and McNulty 2011).…”
Section: Discussionmentioning
confidence: 99%
“…As Kousser and Mullin (2007) observe, the United States is cross-cut by boundaries for elections at the local, state, and federal levels. Besides variation in registration deadlines, U.S. elections differ in myriad ways, such as the presence or absence of voter ID laws (Bentele and O'Brien 2013), the availability of mail ballots, sample ballots, and other information (Wolfinger, Highton, and Mullin 2005;Kousser and Mullin 2007), or the accessibility of polling places (Brady and McNulty 2011). The onus is on the voter to find out about the details, and searching online is now the obvious way to do so.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation